Visfatin and global histone H3K9me levels in colon cancer - Eman A. Al Abdulsalam; Rowyda N. Al Harithy (Annals of Medicine, 2021)
AbstractBackground Visfatin is considered to be a biomarker in various types of cancers, including colon cancer. Moreover, evidence for epigenetic mechanism must be reported for an association between visfatin level and colon cancer. Therefore, this study was designed to investigate the status of visfatin expression and the global histone three modifications in colon cancerous tissue.Methods Colon cancerous tissue and paired adjacent non-cancerous tissue from 30 patients were used to determine the global histone three modifications using Western blot. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to assess visfatin's expression level in tissues.Results The visfatin and the global H3K9me expression levels were significantly higher in colon cancerous tissue than in the paired adjacent non-cancerous tissue.Conclusion The present study makes a crucial noteworthy contribution to visfatin effect on colon cancer development via H3K9me.